Motion Characteristics of Novel Floating Foundation for Offshore Wind Turbine - 李嘉文 唐友刚 王宾 (Transactions of Tianjin University, 2016)
A novel floating foundation to support the NREL offshore 5 MW wind turbine was designed conceptu-ally by combining the characteristics of barge and Spar. The main focus was structural design and hydrodynamic modelling. Based on this novel floating foundation, the hydrodynamic performance was investigated in the fre-quency domain and time domain by using the wave analysis software HydroD and DeepC from Det Norske Veritas. The frequency domain analysis was conducted to investigate the effects of the incident wave angle and water depth. The time-domain analysis was carried out to evaluate the response of the floating foundation under a selected op-erational condition. The hydrodynamic performances of this floating foundation with respect to time series and re-sponse spectra were also investigated in this study.